2021
DOI: 10.1007/s00125-021-05473-9
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin receptor agonist AdipoRon ameliorates renal inflammation in diet-induced obese mice and endotoxin-treated human glomeruli ex vivo

Abstract: Aims/hypothesis Chronic low-grade inflammation with local upregulation of proinflammatory molecules plays a role in the progression of obesity-related renal injury. Reduced serum concentration of anti-inflammatory adiponectin may promote chronic inflammation. Here, we investigated the potential anti-inflammatory and renoprotective effects and mechanisms of action of AdipoRon, an adiponectin receptor agonist. Methods Wild-type DBA/2J mice were fed with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 50 publications
(94 reference statements)
1
13
0
Order By: Relevance
“…While the current study specifically focused on the effects of MIP3a blockade on renal injury in young obese SS LepR mutant rats, we would speculate that similar results would be observed in older SS LepR mutant rats. Inflammation is known to contribute to renal injury in various adult animal models of obesity (Fernández-Sánchez et al, 2011;Lindfors et al, 2021;Wang et al, 2015). To the best of our knowledge, this is the first study to demonstrate a role for MIP3a in the early development of renal injury associated with obesity.…”
Section: Discussionmentioning
confidence: 68%
“…While the current study specifically focused on the effects of MIP3a blockade on renal injury in young obese SS LepR mutant rats, we would speculate that similar results would be observed in older SS LepR mutant rats. Inflammation is known to contribute to renal injury in various adult animal models of obesity (Fernández-Sánchez et al, 2011;Lindfors et al, 2021;Wang et al, 2015). To the best of our knowledge, this is the first study to demonstrate a role for MIP3a in the early development of renal injury associated with obesity.…”
Section: Discussionmentioning
confidence: 68%
“…The molecule berberine enhances adiponectin signaling through AMPK to ameliorate renal pathology in diabetic mice ( 107 ). In animal models of diabetic nephropathy and obesity, the AMPK agonist PF-06409577 and adiponectin receptor agonist AdipoRon reduce proteinuria, inflammation, and renal fibrosis ( 108 110 ). These results suggest that targeting adiponectin receptors or AMPK directly may be beneficial in obesity- and diabetes-related kidney disease.…”
Section: Adipokine Alterations In Obesity and Effects On The Kidneymentioning
confidence: 99%
“…T2DM is characterized by a compromised intestinal barrier and elevated LPS levels, which contribute to systemic and local low-grade inflammation, thereby promoting the progress of diabetes and subsequent DN ( Zihan and Feng, 2016 ; Feng et al, 2019 ). LPS administration was shown to enhance urinary albumin excretion and renal injury ( Sawa et al, 2014 ; Lindfors et al, 2021 ). Several studies showed the increased intestinal permeability and elevated systemic LPS levels in the DN mice model; notably, improving the gut barrier alleviated DN ( Feng et al, 2019 ; Li et al, 2020a ; Gao et al, 2021 ).…”
Section: Compromised Intestinal Barrier and Aberrant Inflammation In ...mentioning
confidence: 99%